Pengaruh karakteristik dan fundamental perusahaan terhadap pengungkapan modal intelektual - DEVIN LEONARD; ITA TRISNAWATI (Jurnal Bisnis dan Akuntansi, 2015)
The purpose of this study to examine the impact of firm size, firm age, type of industry, type of auditor, management ownership, profitability, and leverage on intellectual capital disclosure among non finance companies listed at Indonesia Stock Exchange. ICD ratio is used to determine the intellectual capital disclosure. The study was using 81 non finance company listed in Indonesia Stock Exchange, with a period between 2012 until 2014. The hypothesis were tested using multiple regression to examine the impact of firm size, firm age, type of industry, type of auditor, management ownership, profitability, and leverage on intellectual capital disclosure. The result of this study showed that firm size has impact on intellectual capital disclosure. While the firm age, type of industry, type of auditor, management ownership, profitability, and leverage variables did not have impact on intellectual capital disclosure.